Arthroscopic suture bracing of posterior cruciate ligament in a multiple ligament knee injury – A technical report - Scheck, Jonas (Trauma Case Rep, 2020)
The optimum therapy of a torn PCL in multiligamental-injured knees is controversially discussed in literature. As conservative treatment and PCL reconstruction alone mostly lead to long-term immobilization, we performed a single stage PCL bracing with ACL reconstruction using ACL TightRopes® and Fiber-/TigerTapes® to accelerate back-to-sport after multiligamental knee injury with bicrucial tears. The brace consisted of two FiberTapes which were looped in an ACL TightRope and transosseously fixed with a Dog Bone-Button®. The ACL reconstruction was performed by a fourfolded semitendinosus graft in TightRope® technique. We chose an active rehabilitation-protocol with immediately allowed knee flexion to 90° in an ACL brace. This led to excellent results with resumption of sports after 6 months and good subjective and objective knee stability measured with a KT-1000. Our results hint that our method of bracing a torn PCL in multiligamental knee injuries may lead to faster rehabilitation with comparable knee stability.